Analyzing the Role of Brand Relationship Dimensions in the Development of Brand Community - Pawar, Prafulla Arjun; Raut, Umesh (Indian Journal of Marketing, 2019)
The development of society proficiently acts as a sign of value creation for the formation of new communities and yields fruitful social arrangements. Usually, these communities are constructed through common concerns and shared values. This paper aimed to explore the role of brand relationship dimensions in the development and enrichment of brand community. The present study also analyzed what a brand community is and examined its importance in brand management. The significance of this research extended with providing a base for the understanding of the consumer - brand relationship, which acts as a crucial tool for the development and enhancement of a brand community. The approach involved the findings of the brand community construct roots and building an association between consumer brand relationship dimensions and brand community. The research focused on the modern concept of marketing domain that is brand community and providing an indepth theoretical base to comprehend the brand community construct with consumer brand relationship dimensions. Methodologically, this research tested the reliability and validity of all latent constructs of the study. The study performed multiple regression analysis to understand the role of brand relationship dimensions in the development and empowerment of a brand community. The results of the study confirmed that the brand relationship dimensions, including brand loyalty, brand attachment, and brand engagement positively affected the development and enhancement of brand community; however, the role of each dimension was found to be variable. The findings of this study provided significant implications to academicians and managers.